Successful Endovascular Management of Intraoperative Graft Limb Occlusion and Iliac Artery Rupture Occurred during Endovascular Abdominal Aortic Aneurysm Repair - Lim, Jae Hong (Korean Society for Thoracic and Cardiovascular Surgery, 2014)
For high-risk patients, endovascular aortic aneurysm repair (EVAR) is a good option but may lead to serious complications, which should be addressed immediately. A 75-year-old man with a history of abdominal surgery underwent EVAR for an aneurysm of the abdominal aorta and iliac arteries. During EVAR, iliac artery rupture and graft limb occlusion occurred, and they were successfully managed by the additional deployment of an iliac stent graft and balloon thrombectomy, respectively. We, herein, report a rare case of the simultaneous development of the two fatal complications treated by the endovascular technique.